The Effects of Housing Assistance on Labor Supply: Evidence from a Voucher Lottery - Jacob, Brian A; Ludwig, Jens (American Economic Review, 2012)
This study estimates the effects of means-tested housing programs on labor supply using data from a randomized housing voucher wait-list lottery in Chicago. Economic theory is ambiguous about the expected sign of any labor supply response. We find that among working-age, able-bodied adults, housing voucher use reduces labor force participation by around 4 percentage points (6 percent) and quarterly earnings by $329 (10 percent), and increases Temporary Assistance for Needy Families program participation by around 2 percentage points (15 percent). We find no evidence that the housing-specific mechanisms hypothesized to promote work, such as neighborhood quality or residential stability, are important empirically. (JEL I38, J22, R23, R38)